2002
DOI: 10.1097/00001786-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nurses' Job Satisfaction and Inpatient Satisfaction: An Exploratory Study in a Taiwan Teaching Hospital

Abstract: This exploratory study sought to test the relationship between nurses' job satisfaction and inpatient satisfaction with quality of nursing care in Taiwan. Patient and nurse data were collected from six inpatient care wards in a teaching hospital. Statistical results showed that nurses' general job satisfaction, general feelings of happiness when they are doing their jobs, and their job satisfaction are significantly correlated with at least one of the inpatient satisfaction factors studied, except for the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 8 publications
3
33
0
3
Order By: Relevance
“…The positively skewed attitude toward nursing care found here is consistent with other studies of attitudes toward nurses [5,56,57]. …”
Section: Resultssupporting
confidence: 92%
“…The positively skewed attitude toward nursing care found here is consistent with other studies of attitudes toward nurses [5,56,57]. …”
Section: Resultssupporting
confidence: 92%
“…4; median = 50; mode = 53). The mean up-to-date time of employment as a nurse was 28 years (standard deviation = 8.8; median = 30; mode = 30), and as an occupational nurse -16 years (standard deviation = 10; median = 13; mode = 10).…”
Section: Resultsmentioning
confidence: 99%
“…From the patient's point of view, undoubtedly, one of the important issues is nursing quality. Many surveys show that job satisfaction is a very important nursing quality outcome indicator [4][5][6][7]. The study aimed at general assessment of the Polish OMS system after over ten years of its functioning in the current shape, made by occupational nurses.…”
Section: Resultsmentioning
confidence: 99%
“…[13], in the United States, showed that patients’ sense of confidence and continuity of care were linked to physician satisfaction. In an exploratory study conducted in Taiwan, Tzeng and Ketefian [14] reported that nurses’ satisfaction was positively associated with pain management, explanations regarding care, and courtesy toward patients and their families. Studies have shown correlations between the physician-nurse relationship and mortality rates, medical errors and hospital length-of-stay [15].…”
Section: Introductionmentioning
confidence: 99%